2005
DOI: 10.1002/jctb.1276
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of polycyclic aromatic hydrocarbons: current knowledge and future directions

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a class of organic compounds that have accumulated in the natural environment mainly as a result of anthropogenic activities such as the combustion of fossil fuels. Interest has surrounded the occurrence and distribution of PAHs for many decades due to their potentially harmful effects to human health. This concern has prompted researchers to address ways to detoxify/remove these organic compounds from the natural environment. Bioremediation is one approach that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
367
0
29

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 719 publications
(400 citation statements)
references
References 79 publications
(97 reference statements)
4
367
0
29
Order By: Relevance
“…Taking into account the fact that more than 57 % of the SCS isolates belonged to the genus Pseudomonas, and the fact that the Pseudomonas affiliated 72 bp sized T-RF (Table 3) represented *40 % of the relative abundance in sample SCS, we may assume that the pseudomonads are the most active within highly PAH contaminated environments. This finding is in accordance with reports of other studies which also found the dominance of Pseudomonas species in different PAH impacted environments (Ma et al 2006;Bamforth and Singleton 2005;Johnsen et al 2005;Liu et al 2010). The present study provides further evidence for the overwhelming dominance of proteobacterial and actinobacterial isolates within highly PAH contaminated soils.…”
Section: Discussionsupporting
confidence: 93%
“…Taking into account the fact that more than 57 % of the SCS isolates belonged to the genus Pseudomonas, and the fact that the Pseudomonas affiliated 72 bp sized T-RF (Table 3) represented *40 % of the relative abundance in sample SCS, we may assume that the pseudomonads are the most active within highly PAH contaminated environments. This finding is in accordance with reports of other studies which also found the dominance of Pseudomonas species in different PAH impacted environments (Ma et al 2006;Bamforth and Singleton 2005;Johnsen et al 2005;Liu et al 2010). The present study provides further evidence for the overwhelming dominance of proteobacterial and actinobacterial isolates within highly PAH contaminated soils.…”
Section: Discussionsupporting
confidence: 93%
“…Microbial remediation is one of the most potential technologies for PAHs abatement [12,13]. However, biosorption of PAHs by microorganisms has been ignored in bioremediation practices.…”
Section: Biosorption and Biodegradation Of Phen And Pyr By Fungi P Cmentioning
confidence: 99%
“…Their main source in the environment is of anthropogenic origin, namely combustion of fossil fuels such as petroleum and coal containing considerable amounts of PAHs (Wilcke, 2000;Bamforth and Singleton, 2005). There are also natural pyrogenic sources like vegetation fires or volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%